High performance sport und athlete health - Lemez, S.; Rongen, F. (Routledge handbook of talent identification and development in sport, 2017)
While there are many health benefits associated with involvement in high performance sport (e.g., superior lifespan longevity; Lemez & Baker, 2015), this chapter considers the health consequences. Many youth athletes pursue a career in high performance sport, often through involvement in elite youth or talent development programs. Despite its appeal, concerns have arisen regarding the health impact of this quest for high performance (e.g., Baker, Safai, & Fraser-Thomas, 2015). The purpose ofthis chapter is to review the immediate and long-term physical and psychosocial health outcomes in elite athletes. Such a review is important for identifying health risks associated with involvement in high performance sport and provides important implications for athlete development.